Home Literacy Environment and English as A Second Language Acquisition: A Meta-analysis. Issue 4 (2nd October 2022) - Dong, Yang; Chow, Bonnie Wing-Yin
ABSTRACT: This paper is a quantitative synthesis of research on home literacy environment (HLE) and children's English as a second language (ESL) learning outcomes through a meta-analysis of 18 articles in kindergarten, primary, and secondary school students ( N = 4401) carried out between 2000 and 2018. It examines the associations between HLE factors and children's ESL performance. Results showed the effect sizes between HLE factors and children's ESL performance was small to moderate. Family members shared a similar effect size on children's ESL performance. Parental literacy teaching behaviors have stronger effects on children's ESL ability than parental beliefs on their children's English learning and the availability of learning resources at home. These results highlight the importance of HLE and indicate the relative contributions of specific HLE factors on children's ESL acquisition.